Subsidized Housing Development Strategy in a Green and Sustainable Indonesia - Nugroho, Wahyu; Permana, Dudi; Siswanti, Indra; Ramli, Yanto (Budapest International Research and Critics University, 2022)
The development of green and sustainable housing is the main goal in preserving the environment and nature. The number of subsidized housing developments that increase from year to year will have a significant impact on sustainability. For this reason, the awareness of all stakeholders to make it happen is very important. A precise strategy is needed in stimulating and forcing developers to carry out sustainable housing development by ranking them according to their capital capacity and the availability of skilled workers.